Case Report: New presentation of CLIFAHDD syndrome with a novel variant in the NALCN gene and a literature review - Chen, Yi; Xia, Xiaotong; Zhang, Yiwen; Gao, Li; He, Chenyiyi; Cao, Jianguo (Frontiers in Pediatrics, 2024)
Congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD) syndrome (OMIM#616266) is an autosomal dominant hereditary disease that can lead to the congenital contracture of the limbs and face, hypotonia, and developmental delay. In addition, it may result in the growth retardation and present various clinical symptoms such as brain atrophy, a small pituitary gland, musculoskeletal abnormalities, abnormal breathing, abdominal hernia, and abnormal facial features. Herein, we describe a novel de novo missense genetic variant in the sodium leak channel, nonselective (NALCN) gene that is associated with CLIFAHDD syndrome.This study describes the case of a patient with varus deformities in both feet, deviation of the ulnar side of the fingers, and severe hypotonia. This patient was subsequently confirmed to have CLIFAHDD syndrome through genetic testing, which also revealed a novel missense de novo genetic variant in the NALCN gene (c.3553G>A, p.Ala1185Thr).Our findings further enrich the known variant spectrum of the NALCN gene and may expand the range of clinical options for treating NALCN-related disorders.